1990
DOI: 10.1177/036354659001800508
|View full text |Cite
|
Sign up to set email alerts
|

Anteromedial tibial tubercle transfer without bone graft

Abstract: We followed 30 patients for more than 2 years after anteromedial tibial tubercle transfer for persistent patellofemoral pain associated with patellar articular degeneration. Twelve of these patients were followed more than 5 years. We report 93% good and excellent results subjectively and 89% good and excellent results objectively. The quality of improvement was sustained in all 12 of the patients who were evaluated again after more than 5 years from surgery. When examined separately, 75% of those patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
211
0
7

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(227 citation statements)
references
References 29 publications
9
211
0
7
Order By: Relevance
“…20,21 Anteromedialization of the tibial tubercle is a surgical option for improving patellofemoral alignment. 22 In cases in which there is excessive lateralization of the tibial tubercle, lateral retinacular release alone is not enough to adequately reduce pressure on the lateral facet of the patella, and a tibial tubercle osteotomy is performed. Medializing the tibial tubercle by 10 mm significantly decreases the maximum lateral pressure by 15% to 20% for intact cartilage without overloading the medial cartilage.…”
mentioning
confidence: 99%
“…20,21 Anteromedialization of the tibial tubercle is a surgical option for improving patellofemoral alignment. 22 In cases in which there is excessive lateralization of the tibial tubercle, lateral retinacular release alone is not enough to adequately reduce pressure on the lateral facet of the patella, and a tibial tubercle osteotomy is performed. Medializing the tibial tubercle by 10 mm significantly decreases the maximum lateral pressure by 15% to 20% for intact cartilage without overloading the medial cartilage.…”
mentioning
confidence: 99%
“…Clinical examination: For a dislocation we would expect to find the following clinical signs: 1) knee defor- mation; 2) atrophy of the thigh compared to the opposite healthy thigh; 3) on knee flexion, a prominent lateral knee; the patellar medial glide test < 5 mm at 30 degrees of knee flexion [9]; and 4) the patient being unable to run. We also tested the following factors: Q-angle [10], genu valgum, and the ligament laxity.…”
Section: Methodsmentioning
confidence: 99%
“…The anteromedialisation of the tibial tubercle elevates the distal pole of the patella, which in turn reduces contact on the distal patella during early knee flexion, thus potentially alleviating anterior knee pain symptoms and preventing arthritic progression. Fulkerson and associates reported 93 % good and excellent results subjectively and 89 % good and excellent results objectively [97]. A review of their results demonstrated an overall 74 % of their 42 patients as having good or excellent results at an average of 8.2 years postoperatively [98].…”
Section: Bony Realignment Proceduresmentioning
confidence: 98%